Psicanálise, educação e formação inicial de professores: desafios, articulações e contribuições possíveis - Robaert, Damaris Wehrmann (2017)
This research approaches possibilities and challenges concerning the articulation between areas of Education, Psychoanalysis and Initial Teachers Formation. The primary objective is in understanding the ways in which the psychoanalysis could improve the education and the initial training of teachers of teenagers, given that such an area is focused in thinking subjective aspects that are implicit and related to the formation of the psychic structure. Such aspects, very present in teaching profession, are also often forgotten in the pedagogical practice. Hence, this is a bibliographical research based on the qualitative approach and on Philosophical Hermeneutics (GADAMER, 2004) using them as main guiders. It is based on authors such as Freire (1996, 2014, 2015), Nóvoa (1992, 2009), Imbernón (2010, 2011), García (1999), Gatti (2000, 2010) e Arroyo (2013), of Education and Teachers Formation areas; and, Freud (1913, 1914, 1919, 1925, 1933), Kupfer (2001, 2013), Mrech (1999, 2005), Pereira (2005, 2003), Bacha (2002, 2003), Silva (1994) and Gutierra (2003), of Psychoanalysis area. This research have shown that several authors, such as Freud, have been working on relations between psychoanalysis and education. Although, only a few works have investigated specifically the Psychoanalysis contributions to the initial teacher formation. The main contribution possibilities are mostly related to the understanding of the relational aspects built between teachers and students; of the unconscious phenomena that act in educative contexts, although being not easily perceivable; of implications in considering the concept of subject through the psychoanalysis perspective, such as the changes caused in the way of understanding the learning difficulties; and, of the importance of language as a part of subjects and institutions. Among the major challenges, the impossibilities of anticipating or of knowing posteriorly the effects produced by a room for dialogue in the initial teachers formation have been revealed in the psychoanalysis aspects. In addition, there are difficulties in approaching the same effects in short amount of time and in articulation with the needs felt in teaching practice, contextualizing the studied theory, and not only teaching unrelated concepts of the future teaching practice.